Association between nutritional status, physical activity and digital technologies in adolescents - Santos, Wesley Pereira dos (2024)
According to the WHO, in 2019, physical inactivity affected more than 80% of adolescents worldwide and 83.6% in Brazil. As a result of a sedentary lifestyle and a lack of time for physical activity, adolescents tend to be prone to developing overweight and obesity. The aim of this study was to associate nutritional status with the level of physical activity of adolescents at a public school in the state of Minas Gerais. This was a cross-sectional study of adolescents enrolled in the 6th to 9th grades of elementary school and the 1st to 3rd grades of secondary school, aged 10 or over and under 20. The International Physical Activity Questionnaire (IPAQ) short version was used and anthropometric data on weight and height were collected on site at the school. The data was tabulated in Microsoft Excel Office 2010 and analyzed using descriptive statistics. A total of 101 adolescents took part, with an average BMI of 20.3 kg/m2. 80.2% had the habit of eating in front of the television or other screens, the average daily screen time was approximately 5 hours and 45 minutes and there was a prevalence of BMI associated with moderate physical activity, and it was pointed out that the better the BMI (within the appropriate classification range) the greater the adolescent's interest in regular moderate physical activity. The results obtained contributed to understanding the nutritional status of the population investigated and the factors that may condition it.